Malaria parasitemia and its association with liver function parameters, and lipid profile among malaria-infected adult patients in western Ethiopia: A comparative cross-sectional study - Nigus Checkole; Waqtola Cheneke; Temam Ibrahim; Shiferaw Bekele; Birhane Teklay; Mebrahtu Tefera; Ataklti Gebretsadik; Bisrat Fikadu; Getachew Belay Kassahun (PLoS ONE, 2026)
Background Malaria poses a public health problem because it manifests anemia, renal and liver dysfunction, Jaundice, and dyslipidemia. Therefore, the study aimed to assess malaria parasitemia and its association with liver function parameters and lipid profile in Assosa town, Ethiopia from December 23/2021 to March 4/2022. Methods Institution-based comparative cross-sectional study was conducted among 302 study participants (151 study groups and 151comparison group) who were selected by consecutive sampling technique. Socio-demographic and clinical data were collected using structured questionnaires and entered using Epi Data version 4.6. Venous blood specimen was collected from all study individuals and tested for selected parameters by Cobas 311 automated clinical chemistry analyzer. Descriptive statistics, Pearson’s Chi-square, t-test, and ANOVA were used to assess the association using STATA software version 14. Results A total of 302 study participants comprising 212(70.2%) males were included. Majority (70.86%) of malaria patients were infected with P. falciparum (The parasitic densities were reported with 30.46%, 46.36%, and 23.18% for low, moderate, and high parasitemia, respectively. The mean value of aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, and serum bilirubin was significantly higher in malaria patients than in apparently healthy controls (p < 0.001). However, the mean value of total cholesterol, high-density lipoprotein cholesterol, and low-density lipoprotein cholesterol was significantly lower in malaria patients than controls (P < 0.05). Conclusion and Recommendation Liver function tests and lipid profile should be assessed for malaria infected individuals in order to prevent malaria complications.